Coarse revealed preference - HU, Gaoji (Institutional Knowledge at Singapore Management University, 2018)
We identify necessary and sufficient conditions under which a coarse data set canbe coarsely rationalized by a linear order (or weak order). The conditions are easy tocheck, and efficient algorithms are provided. We apply our theory to investigate theobservable restrictions of several economic models including (1) rational choice withimperfect observation; (2) multiple preferences; (3) monotone multiple preferences; and(4) minimax regret.